Penerapan Teknologi REST Service untuk Integrasi Data Mustahiq Berbasis Service Oriented Architecture (SOA) - Iwan Iskandar (UIN Sultan Syarif Kasim Riau, 2015)
Zakat is the best solution in alleviating poverty. Indonesia has 11.37%. of poor people. It will be a problem in future. High poverty levels can result in increased crime rate. Zakat has the potential to help ease the burden of the poor. This time, many zakat institution have mustahiq data and it potentialy causes the data redudant. This resulted in uneven provision / distribution of alms to the poor. In this research,it makes data integration for some institution of zakat, such as BAZ (Badan Amil Zakat), Lazismu and Rumah Zakat. It analize each business processes to develop rest service as parsing the data. The result, Mustahiq data that has been integrated with each zakat institution. So, it makes easy to distribution of zakat for mustahiq.Keywords: BAZ, Data Integration, Lazismu, Mustahiq, Rest Service, Rumah Zakat